Mejoramiento de tres procesos constructivos en el Condominio Anderes - Anchía-Céspedes, Marcos (Instituto Tecnológico de Costa Rica, 2014)
This project details the application of measurement techniques to improve productivity construction processes. The applied techniques were carried out during the block paste, ceramic paste and plastering of walls, corresponding to the construction of a condominium project in confined masonry, with an approximate area of 209 m² each equal housing and architectural facades. The study describes the process, the productivity and measures of labor, then the analysis were obtained to suggest improvement and provides processes and procedures, the researcher first identifies the activities when building a house; then, from all the listed activities some of them where selected with the opinion of an expert in the field of 209 m². The application of this technique produced results as: Identify activities that have productivity problems. To paste activity of block was obtained that productive work is 30%, 46% tax work, 24% non-productive work. The results obtained in ceramic paste productive work was a 21%, 60% Contributory work, 19% non-productive work. In the plaster walls of productive work 30%, 62% tax work and busywork 8% was obtained. It was determined that in the site design and structural design- the architecture has to merge with the construction to avoid problems and loss of productivity. The measurement techniques are appropriate in the construction industry to improve the processes and the productivity.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2014.
Keywords: Productividad; Construcción; Costos; Muestreo; Análisis; Técnicas